The Improvement Based on the DV-Hop Localization Algorithm for Wireless Sensor Networks - DONG Jing-wei; YANG Guang; LIU Yang; Zhang Tian-qi (Journal of Harbin University of Science and Technology)
As the problems of lower localization accuracy appeared in the traditional DV-Hop algorithm，the author analyzed three main factors that influence the localization accuracy of original DV-Hop algorithm which started from the calculation of the average jump distance in algorithm and the calculation of node coordinates. The author then proposed the calculation method of average jump distance based on the weighted correction of the ＲSSI ( Ｒeceive Signal Strength Indicator ) and the calculation method of unknown node coordinates based on the correction of the total least squares ( TLS) . The simulation result shows that compared to the traditional DV-Hop algorithm，the accuracy of the improved algorithm increased by about 30% in distance measurement as well as rose approximately by 35% in relative localization precision.